From problem-solving to problem-finding : great leaders know how to detect smoke, not just raging fires - Roberto, Michael A. (Pearson Education Pub. as FTPress Delivers, 2010)
"This Element is an excerpt from Know what you don't know: how great leaders prevent problems before they happen (ISBN: 9780131568150) by Michael A. Roberto. You can't solve a problem you don't know exists! Learn how leaders can uncover problems while they're still small enough to solve easily! Great leaders do not simply know how to solve problems. They know how to find them. Leaders at all levels need to become more effective problem-finders"--Resource description page.